2017
DOI: 10.1155/2017/3494867
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress in Patients Undergoing Peritoneal Dialysis: A Current Review of the Literature

Abstract: Peritoneal dialysis (PD) patients manifest excessive oxidative stress (OS) compared to the general population and predialysis chronic kidney disease patients, mainly due to the composition of the PD solution (high-glucose content, low pH, elevated osmolality, increased lactate concentration and glucose degradation products). However, PD could be considered a more biocompatible form of dialysis compared to hemodialysis (HD), since several studies showed that the latter results in an excess accumulation of oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
126
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 96 publications
(132 citation statements)
references
References 117 publications
(121 reference statements)
2
126
1
3
Order By: Relevance
“…Moreover, oxidative stress is considered a hallmark feature of CKD-associated CVDs and contributes to all-cause mortality in this patient population. Also, physiological stress on the body of CKD patients is increased in very early stages of the disease, progresses parallel to the deterioration of renal function and is further exacerbated in patients undergoing dialysis (Liakopoulos et al, 2017. In fact, ESRD patients on both hemodialysis (HD) and peritoneal dialysis (PD) manifest significantly enhanced oxidative stress compared with that of predialysis uremic patients (Liakopoulos et al, 2017.…”
Section: Changes In Cellular Balance Of Reactive Oxygen Species Can Cmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, oxidative stress is considered a hallmark feature of CKD-associated CVDs and contributes to all-cause mortality in this patient population. Also, physiological stress on the body of CKD patients is increased in very early stages of the disease, progresses parallel to the deterioration of renal function and is further exacerbated in patients undergoing dialysis (Liakopoulos et al, 2017. In fact, ESRD patients on both hemodialysis (HD) and peritoneal dialysis (PD) manifest significantly enhanced oxidative stress compared with that of predialysis uremic patients (Liakopoulos et al, 2017.…”
Section: Changes In Cellular Balance Of Reactive Oxygen Species Can Cmentioning
confidence: 99%
“…In CKD patients, a pro-oxidative physiologic state leads to oxidative tissue damage (Cachofeiro et al, 2008;Puchades Montesa et al, 2009;Popolo et al, 2013). Indeed, oxidative stress and damage increase in later stages of CKD and become severe in ESRD patients undergoing HD and PD (Liakopoulos et al, 2017. Several oxidative stress parameters gradually increase when renal disease progresses ( Table 1), suggesting that a decline in renal function may have a direct effect on the worsening of oxidative stress (Dounousi et al, 2006;Khansari et al, 2009).…”
Section: Changes In Cellular Balance Of Reactive Oxygen Species Can Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress is increased at the very early stages of CKD, is augmented in parallel to deterioration of renal function, and is further exacerbated by the hemodialysis (HD) process . It has also been shown that end‐stage renal disease (ESRD) patients on maintenance HD exhibit significantly enhanced OS compared to those on peritoneal dialysis (PD) …”
Section: Introductionmentioning
confidence: 99%
“…7 It has also been shown that end-stage renal disease (ESRD) patients on maintenance HD exhibit significantly enhanced OS compared to those on peritoneal dialysis (PD). 8 During the last two decades, OS has become the center of attention as a novel, nontraditional risk factor for inflammation, atherosclerosis, diabetes mellitus (DM), and CKD progression. 9 The heavy CV burden and the increased mortality risk of HD patients is at least partially explained by the severe OS status seen in these patients.…”
Section: Introductionmentioning
confidence: 99%